Japan's New Order in the Philippines, 1942-1945: A Blueprint for Asia Under Japan - Dery, Luis C. (Philippine Social Sciences Review; Vol. 48 Nos. 1-4 Jan-Dec 1984; Ed. Bernardita R. Churchill, 2012)
see text